COMPARISON OF THE EFFECTIVENESS OF WHATSAPP GROUPS AND WEBSITES AS INFORMATION MEDIA FOR TAM-BASED PPDB - Nurul Chafid; Abdul Halim; Mochammad Darip (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2026)
The development of digital technology has encouraged schools to utilize various platforms to deliver information, particularly in the new student admission process, commonly referred to as PPDB. MIN 7 Tangerang uses WhatsApp Groups and the school website as the primary media for disseminating PPDB information; however, the effectiveness of these two media has not been determined. This study aims to compare the effectiveness of WhatsApp Groups and the website as media for PPDB information using the Technology Acceptance Model (TAM) approach. The study employed a quantitative method supported by qualitative data. Data were collected from 136 parents of admitted students who passed the PPDB selection for the 2024/2025 academic year, all of whom had accessed and used both media. The research instrument consisted of a Likert-scale questionnaire based on TAM constructs along with additional variables. Cronbach’s Alpha was used to test the reliability of the instrument, while validity testing was conducted using Exploratory Factor Analysis (EFA). Furthermore, a paired sample t-test was applied to compare two related conditions, and regression analysis was employed to examine the effect of Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) on technology acceptance. The results indicate that WhatsApp Groups are superior in terms of ease of use, whereas the website demonstrates superiority in terms of usefulness, trust, and user satisfaction. The regression analysis confirms that both PEOU and PU significantly influence technology acceptance, with PU exerting a more effect. In conclusion, WhatsApp Groups and the website play complementary roles in delivering PPDB information.